Business ethics : Managing Corporate Citizenship and Sustainability in the Age of Globalization. - Crane, Andrew, 1968-; Matten, Dirk; Glozer, Sarah; Spence, Laura J., 1968- (Oxford : Oxford University Press, 2019)
How can you be an ethical corporate citizen in an increasingly complex, multiple-stakeholder world? This is the most pressing question facing businesses today, small and large, local and global. 'Business Ethics' is a thorough yet accessible exploration of the main ethical theories and how these apply to the major stakeholders facing this question. Written from a truly international perspective and supported by diverse and innovative learning features, this book provides the tools and concepts necessary to understand and effectively manage ethical challenges wherever you are in the world.
Previous edition: 2016.
Includes bibliographical references and index.
Keywords: Business ethics; Society